Effects of agricultural streptomycin and rhizobacteria Bs 8093 on soil microbial communities estimated by analysis of phospholipid fatty acids - ZHOU, XIAN ZHI; ZHANG, QING WEN; LIU, XIAO XIA (The Indian Journal of Agricultural Sciences, 2026)
Phospholipid fatty acids (PLFAs) analysis was used to investigate the effects of agricultural streptomycin and rhizobacteria Bs 8093 on soil microbial communities in tomato monoculture. Tomato field soil microbial communities were altered by agricultural streptomycin and rhizobacteria Bs 8093 applications. The agricultural streptomycin application reduced aerobes, anaerobes, sulfate-reducers, and gram (-) / gram (+) ratio, but strongly increased the abundance of fungi, arbuscular mycorrhizal fungi (AMF), actinobacteria, protists and the fungi / bacteria ratio. The rhizobacteria Bs 8093 application reduced aerobes, and the gram (-) / gram (+) ratio, but strongly increased the abundance of AMF, actinobacteria, fungi / bacteria ratio. Diversity indices analysis indicated that agricultural streptomycin application significantly reduced the richness, evenness and diversity of the soil microbial communities in tomato monoculture, compared to the Bs 8093 and the control treatments. In conclusion, this study showed that both the structure and the diversity of the tomato field soil microbial communities were clearly affected by a long-term application of agricultural streptomycin and rhizobacteria Bs 8093. Compared to the agricultural streptomycin, rhizobacteria Bs 8093 is environmental friendly, the use of rhizobacteria for crop protection is an attractive approach in the modern system in developing a sustainable agriculture.